Peningkatan Tata Kelola Wilayah Melalui Denah Lokasi Dan Pengembangan Budaya Baca Masyarakat - Ezrah Candra Situmorang; Evita Tri Elandiah; Gita Citra Sari; Ayu Rahamnia; Ega Karunia Utama; Abdussalam Al Akbar; Hendri Alamsyah; Evi Lorita (Universitas Dehasen Bengkulu, 2026)
The Thematic Community Service Program (KKNT) Group XVI of Dehasen University in RT 24 RW 07, Sawah Lebar Village focused on strengthening regional administration and increasing community literacy. The main problems identified were the unavailability of accurate visual representation of the area and low reading interest and literacy access for children in the RT 24 environment. The methods used included participatory mapping to create a location map and the provision of educational literacy corner facilities. The results of the activities showed the availability of a strategic location map as a regional navigation tool and the formation of a literacy corner that became a center for informal learning activities for residents. This program contributed to the effectiveness of regional governance and human resource empowerment through strengthening a reading culture from an early age.